Facile one-step coating approach to magnetic submicron particles with poly(ethylene glycol) coats and abundant accessible carboxyl groups - Long GB (Dove Medical Press, 2013)
Gaobo Long,1,* Xiao-lan Yang,1,* Yi Zhang,1 Jun Pu,2 Lin Liu,1 Hong-bo Liu,1 Yuan-li Li,1 Fei Liao11Unit for Analytical Probes and Protein Biotechnology, Key Laboratory of Clinical Laboratory Diagnostics of the Education Ministry, College of Laboratory Medicine, 2Department of Urology, the First Affiliated Hospital, Chongqing Medical University, Chongqing, People's Republic of China*These authors contributed equally to this workPurpose: Magnetic submicron particles (MSPs) are pivotal biomaterials for magnetic separations in bioanalyses, but their preparation remains a technical challenge. In this report, a facile one-step coating approach to MSPs suitable for magnetic separations was investigated.Methods: Poly(ethylene glycol) (PEG) was derived into PEG-bis-(maleic monoester) and maleic monoester-PEG-succinic monoester as the monomers. Magnetofluids were prepared via chemical co-precipitation and dispersion with the monomers. MSPs were prepared via one-step coating of magnetofluids in a water-in-oil microemulsion system of aerosol-OT and heptane by radical co-polymerization of such monomers.Results: The resulting MSPs contained abundant carboxyl groups, exhibited negligible nonspecific adsorption of common substances and excellent suspension stability, appeared as irregular particles by electronic microscopy, and had submicron sizes of broad distribution by laser scattering. Saturation magnetizations and average particle sizes were affected mainly by the quantities of monomers used for coating magnetofluids, and steric hindrance around carboxyl groups was alleviated by the use of longer monomers of one polymerizable bond for coating. After optimizations, MSPs bearing saturation magnetizations over 46 emu/g, average sizes of 0.32 µm, and titrated carboxyl groups of about 0.21 mmol/g were obtained. After the activation of carboxyl groups on MSPs into N-hydroxysuccinimide ester, biotin was immobilized on MSPs and the resulting biotin-functionalized MSPs isolated the conjugate of streptavidin and alkaline phosphatase at about 2.1 mg/g MSPs; streptavidin was immobilized at about 10 mg/g MSPs and retained 81% ± 18% (n = 5) of the specific activity of the free form.Conclusion: The facile approach effectively prepares MSPs for magnetic separations.Keywords: magnetic submicron particles, carboxyl groups, PEG-bis-(maleic monoester), monomer, radical co-polymerization, steric hindrance